Which outcome variables are associated with psychological inflexibility/flexibility for chronic pain patients? A three level meta-analysis - Fang, Shuanghu; Ding, Dongyan (Frontiers in Psychology, 2022)
The psychological flexibility model can be seen as a basis for an integrated and progressive psychological approach to chronic pain management. Some researchers suggest that psychological flexibility and inflexibility represent distinct processes and constructs. This meta-analysis is the first to provide a summary estimate of the overall effect size for the relationship between psychological (in)flexibility and common outcomes among chronic pain patients. Four databases were searched (PsycINFO; PubMed; Web of Science, CINAHL) along with reference lists. Thirty-six cross-sectional studies were included (7779 participants). Meta-analyses (random effects model) indicated a significant medium negative association between psychological flexibility and pain intensity or functional impairment. The present study also indicated a significant small to medium association between psychological inflexibility and pain intensity, a nearly large association between psychological inflexibility and functional impairment as well as the quality of life, and a large association between psychological inflexibility and anxiety/depression. Due to the limited number of included studies, the relationship between risk behavior and psychological inflexibility may not be significant. Types of countries and instruments measuring psychological inflexibility may explain part of the heterogeneity. These findings may carry significant implications for chronic pain patients regarding the potential relationship between psychological inflexibility or flexibility and these outcomes. It may consequently form the basis for more robust testing of causal and manipulable relationships.